THE INFLUENCE OF COMMUNICATION EFFECTIVENESS ON CONSTRUCTION PROJECT SUCCESS (CASE STUDY: CONSULTANTS AND CONTRACTORS IN WEST JAVA) - Diyanti Santoso, Nur
Communication is considered to have an important role in supporting the achievement of project success. Some previous studies have stated that without well-planned and well-executed communication that lead to communication effectiveness, it will affect the achievement of the expected project results, especially in terms of cost, time, quality of results and quality service. Effective communication in projects means that information is provided in the right format, at the right time, to the right people and with the right impact. Project implementation cannot run smoothly without good communication which can lead to inaccurate information and miscommunication. The worst possibility is that it can lead to project failure. If this is neglected, it is not impossible that the company will experience substantial losses both in terms of financial and corporate image. Therefore, this research is intended to find out the effect of communication effectiveness on project success and also to find out dominant factors affecting project communication. Data was collected using a survey method for this research by distributing online questionnaire. Obtained 79 respondents who are from planning consultants, supervision consultants and contractors with qualifications of medium and large companies, operating and domiciled in West Java. Furthermore, to analyze the data obtained, it will be done by using Simple Linear Regression and Relative Important Index (RII) analysis. In the analysis, it will be divided into 6 categories based on the characteristics of the work, namely: overall (planning consultant, supervisor consultant and contractor), based on the type of business consulting company (planning consultant and supervisor consultant), based on the work environment (supervision consultant and contractor) and each type of company, namely planning consultant, supervision consultant and contractor. The results of the study indicate that the effectiveness of communication has a positive and significant effect on project success and there is a strong relationship between the two. This means that the more effective the communication is, the higher the success rate of the project, which is shown from the regression equation, according to the overall is Y= 1.708+0.593X, planning consultant & supervision consultant is Y= 1.337+0.689X, supervision consultant & contractor is Y=1.815+0.571X, planning consultant is Y=1.579+0.620X, while for supervision consultants is Y=0.998+0.785X and for contractors is Y= 2.136+0.482X. Therefore, if consultants and contractors want to increase the success of the project, it is necessary to pay attention to the effectiveness of the communication that exists in the project. Consultants and contractors assess that communication within the project has been effective, especially by supervisory consultants and contractors. This shows that the communication in the project is better than in the office by the planning consultant. With the most effective communication is in assisting decision making. While the achievement of project success in terms of cost, quality, time, satisfaction, health and safety is considered good. Health and safety performankerjce gets the highest average score in project success and the lowest is time performance. So that it needs to be improved by carrying out proper scheduling, timely execution of work and better supervision. The results also show dominant factor influencing project communication according to the five groups is the Quality of the Project Manager, while according to the supervision consultant is Teamwork and Collaboration. These differences can be caused by the main task of planning consultants and contractors, who plan and carry out projects directly from the beginning to the end of the project, where a Project Manager is needed to lead the amount of work that must be done, communicated and decided on in carrying out the work. As for the supervision consultant, the main task is to supervise and check the work performance and quality of the contractor's work which really requires good teamwork and collaboration in communicating and coordinating well, especially with contractor.